Managing the Lesion and Counseling Patient Post–Breast Biopsy - Raghavan, Bagyam; Gautham, M. V.; Monushree, R.; Kurian, Ann; Geethapriya, Sivaramalingam; Sathyashree, V. (Indographics, 2022)
Breast cancer is the leading cause of cancer deaths worldwide among women. Early diagnosis and prompt treatment offers a chance for cure and long-term survival among afflicted women. Triple assessment which includes clinical examination, radiological imaging and histopathological evaluation has become a standard of care in the evaluation of breast cancer. Radiological imaging involves mammography, ultrasound, and magnetic resonance imaging while pathological evaluation can be done on fine needle, core-needle, and surgical excision biopsy specimens with core needle biopsy being the workhorse for diagnosis. While triple assessment has increased the diagnostic yield and helps in the identification of early lesions, an increasing subset of patients present with a situation where the imaging and pathological characteristics of a lesion do not correlate with each other thereby causing diagnostic and therapeutic dilemma. Imaging and pathology concordance and discordance present distinctly under differing circumstances in the care of the patient. While those with concordant findings proceed to treatment or follow up directly and hence benefit from the early treatment, those with discordant findings are beset with a delay in the diagnosis and should be subjected to further evaluations for confirming or refuting a diagnosis. This article reviews the salient features of image-guided breast biopsy and the outcomes and management options in imaging and pathology concordance and discordance. We also discuss the role of a radiologist in the counselling of the patient before and after receiving the pathological report after biopsy.
Keywords: breast biopsy; core-needle biopsy; postbiopsy management